PERLINDUNGAN HUKUM BAGI PEMBELI YANG BERITIKAD BAIK (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 1696K/PDT/2016) - Michael .; Gunawan Djajaputra (Jurnal Hukum Adigama, 2018)
Legal relationships that occur between legal subjects with each other occurs with the existence of an engagement or agreement. Engagement made rights and obligations in the field of property law for the parties making the agreement. Agreement is made to bind the parties to the agreement. The agreement proves that the legal relationship of the parties is a legal fact. Agreements must born of the will and should be implemented in accordance with the intent of the parties made an agreement in good faith. An agreement starts from a difference or inequality of interest between the parties. The formulation of such agreement relationships is generally always preceded by a negotiation process between the parties. Each agreement is subject to the treaty law, so the agreement must be executed in good faith as set forth in the article 1338 Civil Code or Burgelijk Wetboek (BW). The good faith of contract implementation refers to the objective good faith. The standard used in good faith is an objective standard that refers to an objective norm. In a society often buying and selling that cause various problems, particularly in the sale and purchase of land, among others, the sale and purchase of land owned by others, where the land is not the owner of the seller. As a result of buying and selling like this then the buyer who is honest and good faith will experience disruption to enjoy the goods that  they want to buy.